Rowland Evans papers - Evans, Rowland, 1921-2001.
Correspondence, notebooks, interviews, drafts, transcripts, articles and other writings, research and reference material, subject files, printed matter, and other papers relating to Evans's career as a journalist and political commentator. Includes material relating to his partnership with Robert D. Novak writing the newspaper column Inside Report, hosting their program of political commentary on CNN television, and work as contributing editors for Reader's Digest. Subjects include foreign relations with the Middle East especially Israel and the attack on the USS Liberty (Ship). Represents politicians, administration officials, other public figures, and journalists in the U.S. and chiefly within Washington society.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Journalist and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Novak, Robert D; Cable News Network; Liberty (Ship); Journalists -- United States; Journalists -- Washington (D.C.); Politicians -- United States; Politicians -- Washington (D.C.); Israel -- Foreign relations -- United States; Middle East -- Foreign relations -- United States; United States -- Foreign relations -- Israel; United States -- Foreign relations -- Middle East; United States -- Officials and employees; United States -- Politics and government -- 20th century; Authors; Journalists